Excepcionalidad del marco regulatorio para combatir la desinformación mediante fake news en el Perú: el estándar constitucional del intercambio de ideas frente al fenómeno de la conectividad globalizada - Castillo Lozada, Gabriel David (2023)
|n this thesis, the author analyzes the constitutional character of a regulatory framework against fake news in Peru in accordance with the constitutional block, the current legal standard of freedom of expression and its external limits. In this sense, it shows the deficiencies of the soft law, derived from the self-regulation of the media, proposing the application of other suitable means to combat disinformation in Peru. Likewise, it reviews the legislative advances in Comparative Law in order to contrast them in the light of the provisions of international treaties and revealing their excesses in relation to the right to freedom of speech, as well as the technical and legal deficiencies in the draft of the legal assumptions. Then, it explains the legal reasons for applying Criminal Law to fake news and partly discards the constitutional standard of the exchange of ideas as an obstacle to its regulation. Based on the points mentioned, it proposes a specific criminal regime to penalize the repeated dissemination of fake news, it defines legally and technically the phenomenon in question, establishes the assumptions for the criminal action’s exceptional fair, the conditions for the graduation of the penalty and the systematic interpretation in harmony with the sources of law.